(untitled) (Scientific journal of the Fergana State University, 2026)
An important place in the system of economic relations between Uzbekistan and foreign countries is occupied by the introduction of foreign investments in industries and sectors of the economy. When attracting foreign investment to the republic, the natural opportunities of the Navoi, Bukhara and Samarkand regions stand out among other regions of the republic, special attention is paid to the creation of joint ventures, special attention is paid to attracting foreign investment.